Indigenous Women, Water Justice and Zaagidowin (Love) - McGregor, Deborah (Osgoode Digital Commons, 2015)
I would like to open by saying Chi-miigwech (a big thank-you) to those Elders/Grandmothers who have shared their stories and teachings with me over the years. Some have since passed on and I hope that through my words, their love and generosity will continue the process of healing the people and waters upon which they so integrally depend. The paper which follows contains many references to notions of love, mutual respect, and responsibility towards the natural world, and water in particular. These ideas may seem a little tenuous for a serious paper on a critical environmental justice issue, but concepts of love, kindness and generosity are not naive ideals in Anishinaabek society. These obligations and relationships are living examples of Anishinaabek natural law. They are principles that have enabled us to thrive for millennia, and may in fact prove to be of the utmost relevance in our quest for sustainability.